2017
DOI: 10.1038/s41598-017-16689-4
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous white adipocytes express a light sensitive signaling pathway mediated via a melanopsin/TRPC channel axis

Abstract: Subcutaneous white adipose tissue (scWAT) is the major fat depot in humans and is a central player in regulating whole body metabolism. Skin exposure to UV wavelengths from sunlight is required for Vitamin D synthesis and pigmentation, although it is plausible that longer visible wavelengths that penetrate the skin may regulate scWAT function. In this regard, we discovered a novel blue light-sensitive current in human scWAT that is mediated by melanopsin coupled to transient receptor potential canonical cation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 45 publications
(47 reference statements)
1
43
0
4
Order By: Relevance
“…In humans, it has been reported that OPN4 is expressed in subcutaneous white adipose tissue and in blood vessels as a peripheral tissue and that lipolysis is facilitated and blood vessels are dilated by blue light irradiation (Ondrusoval et al, ; Sikka et al, ). These suggest that OPN4 functions even in peripheral tissues, and thus, it is not surprising that OPN4 is expressed and has some functions in skin tissue.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, it has been reported that OPN4 is expressed in subcutaneous white adipose tissue and in blood vessels as a peripheral tissue and that lipolysis is facilitated and blood vessels are dilated by blue light irradiation (Ondrusoval et al, ; Sikka et al, ). These suggest that OPN4 functions even in peripheral tissues, and thus, it is not surprising that OPN4 is expressed and has some functions in skin tissue.…”
Section: Discussionmentioning
confidence: 99%
“…To date, however, there are only a few suggestions of extraocular light reception in mammals. Notably, it has been shown that non-visual opsins function within cultured adipocytes (Ondrusova et al, 2017), and within cultured skin cells (Regazzetti et al, 2018) and can also mediate a vasorelaxation response (Sikka et al, 2014(Sikka et al, , 2016.…”
Section: Discussionmentioning
confidence: 99%
“…It has previously been suggested that melanopsin (OPN4) can mediate light responses in cultured primary adipocytes (Ondrusova et al, 2017). This suggested the interesting possibility that OPN3 and OPN4, both blue light responsive, might act in concert to regulate white adipocyte lipolysis.…”
Section: White Adipocyte Opn3 Is Required For Normal Lipolysis Duringmentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned above, very recently, the melanopsin presence was discovered in subcutaneous white adipocytes. In these cells, similar to ipRGCs, the signaling cascade is mediated by both TRPC and PLC as delivery of inhibitor of melanopsin (opsinamide), inhibitor of TRPC channels (clemizole) or of PLC (U73122) inhibited light‐induced current in vitro in these cells .…”
Section: Melanopsin‐regulated Signaling Pathwaymentioning
confidence: 99%